Energy Dissipation in Molecular Systems - Tramer, André; Jungen, Christian; Lahmani, Françoise; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2005)
Energy Dissipation in Molecular Systems analyzes experimental data on the redistribution and dissipation of energy injected into molecular systems by radiation or charged particles. These processes, competing with such practically important relaxation channels as chemical reaction or stimulated emission (laser action), are the primary focus in this monograph. Among other topics, the book treats vibrational redistribution and electronic relaxation in isolated molecules and the effects of inter-molecular interactions (collisions, complex formation, solvent effects) on the relaxation paths. Primary photo-chemical processes (such as isomerization, proton or hydrogen-atom transfer, electron transfer and ionization) are also treated as particular cases of vibrational or electronic relaxation. Only a basic knowledge of quantum mechanics and spectroscopy is assumed and calculations are kept to a strict minimum, making the book more accessible to students.
The Basic Notions -- Experimental Techniques -- Intramolecular Vibrational Redistribution -- Vibrational and Rotational Relaxation -- Electronic Relaxation -- The Electron and Proton Transfer -- Postface.
Keywords: Atoms; Physics; Continuum physics; Physical chemistry; Engineering; Atomic, Molecular, Optical and Plasma Physics; Classical and Continuum Physics; Physical Chemistry; Engineering, general